Hemorrhage Rates From Brain Arteriovenous Malformation in Patients With Hereditary Hemorrhagic Telangiectasia. Issue 5 (May 2015) - Kim, Helen; Nelson, Jeffrey; Krings, Timo; terBrugge, Karel G.; McCulloch, Charles E.; Lawton, Michael T.; Young, William L.; Faughnan, Marie E.; Chakinala, Murali; Gossage, James R.; Henderson, Katharine; Iyer, Vivek; et al.
Abstract : Background and Purpose—: Hereditary hemorrhagic telangiectasia (HHT) is a systemic disease characterized by mucocutaneous telangiectasias, epistaxis, and arteriovenous malformations (AVMs). Intracranial hemorrhage (ICH) rates in this population are not well described. We report ICH rates and characteristics in HHT patients with brain AVMs (HHT-BAVMs). Methods—: We studied the first 153 HHT-BAVM patients with follow-up data enrolled in the Brain Vascular Malformation Consortium HHT Project. We estimated ICH rates after BAVM diagnosis. Results—: The majority of patients were women (58%) and white (98%). The mean age at BAVM diagnosis was 31±19 years (range, 0–70), with 61% of cases diagnosed on asymptomatic screening. Overall, 14% presented with ICH; among symptomatic cases, 37% presented ruptured. During 493 patient-years of follow-up, 5 ICH events occurred yielding a rate of 1.02% per year (95% confidence interval, 0.42–2.44%). ICH-free survival differed significantly by ICH presentation ( P =0.003); ruptured cases had a higher ICH rate (10.07%; 95% confidence interval, 3.25–31.21%) than unruptured cases (0.43%; 95% confidence interval, 0.11–1.73%). Conclusions—: Patients with HHT-BAVM who present with hemorrhage are at a higher risk for rehemorrhage compared with patients with BAVM detected presymptomatically. Abstract : Supplemental Digital Content is available in the text.